The Effect of Servant Leadership and Job Satisfaction on Organizational Commitment Mediated by Job Loyalty in Early Childhood Education - Wijaya, Yeny; Wibawanta, Budi (Universitas Negeri Padang, 2025)
This study aims to determine the influence of servant leadership on organizational commitment, job loyalty, job satisfaction on organizational commitment, job satisfaction, job satisfaction on job loyalty, and organizational commitment to job loyalty. In addition, this study also examines the influence of servant leadership and job satisfaction on organizational commitment through job loyalty. The method used is a descriptive study with hypothesis testing using a causal design, analyzed through a Partial Least Square (PLS). The results showed that there was no significant influence between servant leadership and organizational commitment. However, there is a significant positive influence between servant leadership and work loyalty, where the higher the value of servant leadership, the higher the work loyalty, and vice versa. In addition, there is a significant positive influence between job satisfaction and organizational commitment, where the higher the job satisfaction score, the higher the organizational commitment, and vice versa. Significant positive influences were also found between job satisfaction and job loyalty, as well as between job loyalty and organizational commitment. Job satisfaction and servant leadership have a significant positive influence on organizational commitment through job loyalty, where job loyalty can be an intervening variable between job satisfaction and organizational commitment, as well as between servant leadership and organizational commitment.